A Critical Evaluation of the Use of Crack Width Requirements in the Durability Design of Marine Reinforced Concrete Structures - Elias, Nicholas (Department of Civil Engineering, 2024)
Crack width requirements (CWRs), which aim to limit cracks in reinforced concrete (RC) to maximum prescribed values, play a major – and often dominant – role in the design of marine RC structures. However, there are several issues with the current CWRs, chief among which is the fact that, despite decades of research, no clear relationship between crack width and steel reinforcement corrosion rate in concrete has been found. Instead, there exist two opposing schools of thought in the literature – one which says that there is a relationship between crack width and reinforcement corrosion rate, and one which argues that no such relationship exists – with good evidence to support both schools of thought. Recent research has shown that even small cracks, with widths below the required values, may lead to extensive corrosion. It is therefore uncertain whether designing for the CWRs actually improves durability and extends the service life of marine RC structures. Furthermore, the use of the CWRs, which frequently results in large increases in the required amount of reinforcing steel, may lead to significant increases in the cost and environmental impact of marine RC structures. Yet, to date, these impacts have not been quantified. In order to address these issues, this study was aimed at evaluating the effect of designing to meet the current CWRs on the durability, cost, and environmental sustainability of marine RC structures. This was done by designing two sets – one with, and one without the CWRs – of typical marine RC structural elements. Based on real industry projects, two different types of elements were designed – a crane rail beam for a coal export jetty in Matola, Mozambique, and a precast crown wall unit for a breakwater in Rupert's Bay, St. Helena Island. The designs were carried out using a combination of BS 6349 and EN 1992-1-1:2004, as these are the codes of practice typically used in the South African coastal engineering industry. The effects of designing for the current CWRs on durability, cost, and environmental sustainability were then quantified by carrying out service life modelling, life cycle cost assessments (LCCAs) and estimating embodied carbon (EC) values for the designed members. The results of the service life modelling show that, for the range of crack widths likely to occur in practice, the use of the current CWRs does not improve durability, and may even reduce service life, as they encourage the use of more, smaller diameter reinforcement bars, which has the effect of increasing corrosion rate and reducing the time taken for a critical amount of the reinforcement to be lost due to corrosion. Furthermore, the results of the LCCA and EC estimates imply that the current CWRs are not the most cost-effective method for durability design and may result in significant increases in cost and environmental impact. Taken together, these results suggest that, even if a relationship is assumed to exist between crack width and corrosion rate, the current CWRs are neither the most effective, nor efficient way of addressing the effects of cracking on the durability of marine RC structures. It is therefore recommended that the current crack width requirements should be removed from the durability design codes of practice and replaced with either a limitation on steel stress, a more lenient crack width requirement (for example, of 0.5 mm rather than 0.3 mm), or a performance-based crack width requirement, which takes better account of the complexity of cracking and its effect on durability. It is also recommended that engineers be given the option to use other methods of providing durability, such as the use of crack-sealing and waterproofing admixtures, or hydrophobic treatments, instead of the current CWRs. However, before any of these recommendations can be implemented, the results of this study need to be confirmed with further research. Owing to the limitations of both service life modelling and accelerated laboratory corrosion, it is recommended that this further research should take the form of an extensive evaluation of the durability performance of existing marine RC structures.